Analisis Prokrastinasi Akademik Mahasiswa (Studi Pada Mahasiswa Jurusan Psikologi Pendidikan Dan Bimbingan Fakultas Ilmu Pendidikan) - Abdul Saman (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This study aims to examine students' academic procrastination. The approach used is a quantitative approach with descriptive research type. The study variable is the student's academic procrastination by measuring aspects of delay for initiating and completing tasks, delays in tasks, time gaps between actual plans and performance, and performing more enjoyable activities. The higher the score obtained the higher the frequency of students in doing academic procrastination, and vice versa. Sampling using simple random sampling technique with a sample of 230 people from a total population of 349 people. Technique of collecting data is done through three characteristic that is stimulus, psychology attribute and response then data analyzed with descriptive analytical technique. Based on the result of the research shows that the level of academic procrastination of the students of Faculty of Education Universitas Negeri Makassar is 0 people in very high category, 25 people are in high category, 84 people are in medium category, 99 people are in low category, and 22 people are in very low category. These results indicate that the level of postponing behavior of students for MARPs is low.